Mindset and Religiosity among Elementary, Middle, and High School Graduating Students - Anito, Henok Daniel (SUMIKOLAH: Jurnal Ilmu Pendidikan, 2025)
This study examined the relationship between mindset and religiosity among graduating students from grades 6, 9, and 12 in one private international school in Indonesia. It also investigated potential differences in mindset and religiosity based on gender, grade level, and religious affiliation. Non-parametric tests were used in data analysis. Findings revealed a slightly more prevalent growth mindset and a moderate level of religiosity among the sampled students. While a weak negative correlation between religiosity and mindset is noted, it was not statistically significant. There were no significant differences in mindset and religiosity based on gender and grade level. However, there was a significant difference in religiosity based on religious affiliations, particularly between Buddhist and Christian students. Although mindset remained consistent across religious affiliations, implications suggest the need for educational approaches that consider religious and cultural contexts in fostering holistic student development.